2020
DOI: 10.5334/ijc.961
|View full text |Cite
|
Sign up to set email alerts
|

Institutions for Collective Gardening: A Comparative Analysis of 51 Urban Community Gardens in Anglophone and German-Speaking Countries

Abstract: Groups of urban gardeners collectively grow vegetables, fruits and flowers in an increasing number of community gardens all over the world. Despite a growing body of literature on community gardens, there is a particular gap for a transcontinental bigger N-study on the organisation of community gardening, which we want to fill with a comparative document analysis of 51 urban community gardens in six anglophone and German-speaking countries. Specifically, we want to understand how community gardens are organise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Community garden is a term with a rich connotation, and there is no single blueprint for the organization of CGs [75]. Škamlová et al [76] argue that there is a strict distinction between CGs and allotment gardens in previous literature.…”
Section: The Types Of Gardens Included In Our Search Strategymentioning
confidence: 99%
“…Community garden is a term with a rich connotation, and there is no single blueprint for the organization of CGs [75]. Škamlová et al [76] argue that there is a strict distinction between CGs and allotment gardens in previous literature.…”
Section: The Types Of Gardens Included In Our Search Strategymentioning
confidence: 99%
“…Accordingly, the traditional grasp of organizational hierarchies and power relations might be dissolved completely (Aptekar, 2015). In this context, Göttl & Penker (2020) conducted a comparative analysis of 51 urban community gardens in Anglo-Saxon and German-speaking countries. The authors acknowledge that not a single blueprint exists for organizing CG.…”
Section: Agriculturementioning
confidence: 99%
“…Fox-Kämper et al (2018) reviewed CGs in several countries and found that CG governance structures could be classified into three major approaches: top-down, bottom-up, and mixed; however, this classification is a continuum, as there are cases of top-down approaches using community help and bottom-up approaches with political (or administrative), professional, or informal supports. These governance structures also change over time as the garden progresses through the planning, design, implementation, and management phases; furthermore, this process is affected by the place-specific context of each CG (Drake & Lawson, 2015;Fox-Kämper et al, 2018;Göttl & Penker, 2020;Johnson et al, 2019;Škamlová et al, 2020). Thus, it is important to examine each case in order to determine 'who' from 'where' became involved in a given CG project, how this actor's involvement came about, and what is being done by this actor.…”
Section: Core Ideasmentioning
confidence: 99%